The association between interdigital pilonidal sinus and animal groomers is a historical narrative correlation and not a true occupational hazard - Al Shenawi, Hamdi; Yaghan, Rami; Al Saad, Suhair; Binayfan, Ziyad M.; Mohamed, Yaqoob Y.; Alnasser, Mansour M.; Al Shenawi, Fatima; Yaghan, Lamees; Almarabheh, Amer; Alshammari, Abdulrahman; Al Shenawi, Noor; Naguib, Yahya M. (Frontiers in Environmental Health, 2024)
A pPilonidal sinus (PNS) is a small hole or 'tunnel' in the skin that frequently occurs in the sacrococcygeal region. It Nevertheless, PNS can has been reported to occur elsewhere in the body, such as between the fingers (interdigital) in barbers, hairdressers, and animal groomers. The aim of Thisthis study aims was to estimate the prevalence of interdigital PNS among animal handlers in Bahrain and to treat any patients encountered. This is a cross-sectional study with convenience sampling from November 2020 to October 2021. The study participants are were animal handlers from stables, veterinary, and pet shops in Bahrain. There were 43 males and 7 females with direct animal contact. 86% of the study population were handling horses, and 15% were handling different types of animals. No positive cases of interdigital PNS among participants were found, this might reflect the positive impact of good personal hygiene among our study population. Our study shows that groomers in Bahrain frequently wash their hands after handling animals, and 98% have a daily habit of bathing after work. It was also estimated that 60% of the participants use gloves to handle animals themselves or their waste. This is could be the first study looking at the prevalence of interdigital PNS in animal groomers worldwide. However, theThe absence of any case report of interdigital PNS among hair animal groomers in the recent literature strengthens our assumption might suggest that the association between interdigital PNS and hair grooming could be a narrative coincidence rather than a true occupational hazard. The present work may help in better understanding of occupation-disease association, and highlights the importance of mass screening of animal handlers for occupation-dependent health problems.